31.6k views
4 votes
Prove that A(BC)=(AB)C as the associative law of matrix multiplication​

1 Answer

3 votes

Answer:


A\left(BC\right)=\begin{pmatrix}7&13\\ \:15&29\end{pmatrix}


\left(AB\right)C=\begin{pmatrix}7&13\\ \:15&29\end{pmatrix}

Therefore, we conclude that


A(BC)=(AB)C

Explanation:

Given that the associative law of matrix multiplication​


A(BC)=(AB)C

Let


A=\begin{pmatrix}1&2\\ 3&4\end{pmatrix}


B\:=\:\begin{pmatrix}1&0\\ 1&2\end{pmatrix}


C=\begin{pmatrix}1&3\\ \:1&1\end{pmatrix}

proving

A(BC)=(AB)C

Determining the L.H.S

  • A(BC)


A\left(BC\right)=\begin{pmatrix}1&2\\ \:\:3&4\end{pmatrix}\:\left[\:\begin{pmatrix}1&0\\ \:\:\:1&2\end{pmatrix}\begin{pmatrix}1&3\\ \:\:\:\:1&1\end{pmatrix}\right]\:

First determining BC

as multiplying the rows of the first matrix by the column of the second matrix


BC=\begin{pmatrix}1&0\\ \:1&2\end{pmatrix}\begin{pmatrix}1&3\\ \:1&1\end{pmatrix}=\begin{pmatrix}1\cdot \:\:1+0\cdot \:\:1&1\cdot \:\:3+0\cdot \:\:1\\ \:1\cdot \:\:1+2\cdot \:\:1&1\cdot \:\:3+2\cdot \:\:1\end{pmatrix}


=\begin{pmatrix}1&3\\ 3&5\end{pmatrix}

so the matrix equation becomes


A\left(BC\right)=\begin{pmatrix}1&2\\ \:\:3&4\end{pmatrix}\begin{pmatrix}1&3\\ \:3&5\end{pmatrix}


=\begin{pmatrix}1\cdot \:1+2\cdot \:3&1\cdot \:3+2\cdot \:5\\ 3\cdot \:1+4\cdot \:3&3\cdot \:3+4\cdot \:5\end{pmatrix}


=\begin{pmatrix}7&13\\ 15&29\end{pmatrix}


A\left(BC\right)=\begin{pmatrix}7&13\\ \:15&29\end{pmatrix}

Determining the R.H.S

  • (AB)C


\left(AB\right)C=\left[\begin{pmatrix}1&2\\ \:\:\:\:3&4\end{pmatrix}\:\begin{pmatrix}1&0\\ \:1&2\end{pmatrix}\right]\begin{pmatrix}1&3\\ \:\:\:\:\:1&1\end{pmatrix}\:

First determining AB

as multiplying the rows of the first matrix by the column of the second matrix


AB=\begin{pmatrix}1&2\\ \:\:3&4\end{pmatrix}\begin{pmatrix}1&0\\ \:\:1&2\end{pmatrix}=\begin{pmatrix}1\cdot \:\:1+2\cdot \:\:1&1\cdot \:\:0+2\cdot \:\:2\\ \:3\cdot \:\:1+4\cdot \:\:1&3\cdot \:\:0+4\cdot \:\:2\end{pmatrix}


=\begin{pmatrix}3&4\\ 7&8\end{pmatrix}

so the matrix equation becomes


AB\left(C\right)=\begin{pmatrix}3&4\\ \:\:7&8\end{pmatrix}\begin{pmatrix}1&3\\ \:\:1&1\end{pmatrix}

multiplying the rows of the first matrix by the column of the second matrix


=\begin{pmatrix}3\cdot \:1+4\cdot \:1&3\cdot \:3+4\cdot \:1\\ 7\cdot \:1+8\cdot \:1&7\cdot \:3+8\cdot \:1\end{pmatrix}


=\begin{pmatrix}7&13\\ 15&29\end{pmatrix}

Thus,


\left(AB\right)C=\begin{pmatrix}7&13\\ \:15&29\end{pmatrix}

as


A\left(BC\right)=\begin{pmatrix}7&13\\ \:15&29\end{pmatrix}


\left(AB\right)C=\begin{pmatrix}7&13\\ \:15&29\end{pmatrix}

Therefore, we conclude that


A(BC)=(AB)C

User Enterx
by
5.8k points